Effect of molybdenum treatment on the element uptake of plants in a long-term experiment - Puskás-Preszner, Anita; Kovács, Béla; Andrási, Dávid; Burján, Zita Kata (Acta Agraria Debreceniensis, 2012)
Molybdenum as a constituent of several inmportant enzymes is an essential micorelement. It can be found in all kind of food naturally at low level, however, environmental pollution, from natural or anthropogenic sources, can lead to high level of the metal in plants. Our study is based on the long-term field experiments of Nagyhörcsök, where different levels of soil contamination conditions are simulated. Plant samples were collected from the experiment station to study the behaviour of elements: uptake by and transport within the plants, accumulation in different organs, phytotoxicity and effects on the quantity and quality of the crop. In this work we present the effect of molybdenum treatment on the uptake of other elements. Molybdenum is proved to be in an antagonist relationship with copper and sulphur, while molybdenum-phosphorus is a synergist interaction. However, in most of the plants we studied increasing molybdenum-treatment enhanced cadmium-uptake. We have found the most significant cadmium-accumulation in the case of pea, spinach and red beet.